Student Perceptions of Corrective Feedback Methods for Student’s Descriptive Writing in the Course Schreiben Auf Deutsch - Dita Putri Prastiti; Sawitri Retnantiti (Universitas Negeri Malang, 2026)
This study aims to describe students’ perceptions of the implementation of corrective feedback methods, including indirect written corrective feedback from instructors, direct written corrective feedback from peers, and oral corrective feedback from instructors. The data sample consisted of 71 German Language Education students from A, B, and C classes of 2024 cohort who were enrolled in the course Schreiben Auf Deutsch. This study employed a descriptive qualitative method using a questionnaire as the research instrument. The results indicate that instructors provide corrective feedback in both written and oral forms. Students showed positive responses to corrective feedback, such as increased motivation, critical thinking skills, speaking and writing abilities, and an understanding of where errors occurred and how to correct them. Negative responses also emerged, such as feelings of nervousness, laziness, and a lack of self-confidence.